Implementasi Kebijakan Penanggulangan Stunting oleh Dinas Kesehatan di Kabupaten Seram Bagian Barat - Yeyen Yeyen; Pieter Sammy Soselisa; Hengky Virgo Richardo Pattimukay (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The objective of this research is to understand how the stunting reduction policy is implemented by the Health Office in West Seram Regency. The issue to be addressed in this research is: How is the implementation of the stunting reduction policy by the Health Office in West Seram Regency? This research involved eight informants. Data were collected through in-depth interviews, observation, and documentation. The collected data were analyzed using a descriptive qualitative analysis technique with a case study approach. Based on the policy implementation theory by Edward III, which includes four variables: Communication, Resources, Disposition, and Bureaucracy. The findings of this research indicate that the implementation of the stunting reduction policy has been carried out, but it is not yet optimal. In terms of communication, policy communication has been conducted through various media, but it has not reached the entire community. Limited resources, especially nutrition personnel and supporting facilities, are the main obstacles. The disposition of implementers is fairly good, but the lack of incentives hampers work motivation. Regarding bureaucracy, the appointment process of bureaucrats is carried out based on competence with reporting systems through the e-PPGBM application, but cross-sectoral coordination remains ineffective.